Solution of socio-economic efficiency of public projects under the conditions of variable amount of subsidy - Jiříček, Petr; Dvořáková, Stanislava (Univerzita Pardubice, 2019)
The paper will deal with modelling cash-flows of public investment projects under the conditions of variable amount of subsidy from public funds. A deterministic model based on a rational fractional function will be used to assessment of socioeconomic efficiency of public projects subsidized from the European funds. In the model, we will examine the influence of the amount of the subsidy and critical changes of socio-economic cash-flows generated by a project on assessing public investments. We will use the European Union methodology for assessing socio-economic evaluation of project utility by means of cost-benefit analysis. The results of the crisis scenario analysis of the model in the Maple program created on the basis of the concept of Economic net present value (ENPV) and Economic internal rate of return (ERR) will be presented in 2D projection and evaluated by means of the ENPV function depending on the project parameters. The paper will also present using the model for stress test of socio-economic efficiency of innovation project from sphere digitalization of public government, and broadens so far published research.
Keywords: public projects; socio-economic efficiency; the ENPV Function; ERR; subsidy from European funds; cost-benefit analysis; C20; H43